2021
DOI: 10.1007/s00181-021-02052-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country connectedness in inflation and unemployment: measurement and macroeconomic consequences

Abstract: We bring the notion of connectedness (Diebold and Yilmaz, Int J Forecast 28(1):57-66 2012) to a set of two critical macroeconomic variables as inflation and unemployment. We focus on the G7 economies plus Spain, and use monthly data-highfrequency data in a macro setting-to explore the extent and consequences of total and directional volatility spillovers across variables and countries. We find that total connectedness is larger for prices (58.28%) than for unemployment (41.81%). We also identify asymmetries pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…They then use the short-run Phillips curve to build a model that describes the inverse relationship between the number of COVID-19 infections and economic inactivity. Pham and Sala [ 44 ] studied the effect of inflation and unemployment rates on cross-country connectedness for the G7 countries. They found that the connectedness of inflation is high, but unemployment is low.…”
Section: Introductionmentioning
confidence: 99%
“…They then use the short-run Phillips curve to build a model that describes the inverse relationship between the number of COVID-19 infections and economic inactivity. Pham and Sala [ 44 ] studied the effect of inflation and unemployment rates on cross-country connectedness for the G7 countries. They found that the connectedness of inflation is high, but unemployment is low.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the interconnectedness of macroeconomic variables in a globalized world can lead to endogeneity issues [109][110][111]. Endogeneity occurs when the variables under investigation are interdependent, making it difficult to determine which variable is driving changes in the others.…”
Section: Internal Validity Limitations and Macroeconomic Trendmentioning
confidence: 99%
“…• Unemployment -Unemployment refers to the number of people out of work and actively seeking employment (Pham & Sala, 2021). Unemployment can impact the insurance sector in several ways.…”
Section: • Factors Onmentioning
confidence: 99%